Bibliometric analysis: Trends research application of information technology in university libraries - Ramadani, Tri Asti Sukma; Erwina, Wina (Faculty of Communication, Padjadjaran University, 2025)
Background: Technological developments are keeping pace with the increasingly complex needs of society. For example, in university libraries, academics demand information technology to effectively support learning and research activities.Purpose: To analyze publication development, country distribution, the most productive authors, and publication theme trends based on the co-occurrence of keywords related to the research topic.Methods: This study uses quantitative analysis with bibliometric data from the Scopus database and the VOSviewer application.Results: This study shows an increase in publications related to the topic of information technology application in university libraries in 2021. This was influenced by the COVID-19 pandemic, which necessitated information technology-based online services to meet the needs of the academic community. However, publications declined again in 2025 as the research focus shifted to AI and other emerging issues, aligning with current trends. The country with the highest contribution was China, and the most productive author, Chen, Y., also came from China. This can be attributed to the Chinese government's push to accelerate the digitization of higher education. The most frequently discussed keywords were 'information technology,' 'university libraries,' and 'libraries.' Meanwhile, 'smart libraries' was one of the least researched keywords.Conclusion: This study concludes that developing information technology in university libraries is important for creating more efficient, effective, sustainable, and up-to-date services. Future research could analyze similar keywords using different databases or explore rarely researched keywords to obtain more diverse results.